2014
DOI: 10.1007/s00421-014-2995-6
|View full text |Cite
|
Sign up to set email alerts
|

The right ventricle following ultra-endurance exercise: insights from novel echocardiography and 12-lead electrocardiography

Abstract: Purpose: There is contradictory evidence related to the impact of ultra-marathon running on right ventricular (RV) structure and function. Consequently, the aims of this study were to; 1) comprehensively assess RV structure and function before and immediately following a 100 mile ultramarathon in highly trained runners, 2) determine the nature of RV recovery 6 hours post-race, and 3) document 12-lead electrocardiogram (ECG) changes post-exercise.Methods: Echocardiography and 12-lead ECG were assessed in 15 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
1
20
1
Order By: Relevance
“…Kucher and colleagues (2003) presented similar 12-lead ECG findings in patients following pulmonary embolism and suggest that this was consistent with RV strain (Kucher et al 2003) and these finding are also supported by data from Lord et al (2014) where similar repolarization changes are evident in the presence of a marked elevation in RV afterload. There was a significant increase in QTc interval, with 11 athletes meeting criteria for long QT syndrome following the race.…”
Section: Standard 12 Lead Ecgmentioning
confidence: 65%
See 1 more Smart Citation
“…Kucher and colleagues (2003) presented similar 12-lead ECG findings in patients following pulmonary embolism and suggest that this was consistent with RV strain (Kucher et al 2003) and these finding are also supported by data from Lord et al (2014) where similar repolarization changes are evident in the presence of a marked elevation in RV afterload. There was a significant increase in QTc interval, with 11 athletes meeting criteria for long QT syndrome following the race.…”
Section: Standard 12 Lead Ecgmentioning
confidence: 65%
“…A recent study by our research group (Lord et al, 2014) assessed 12-lead electrocardiogram (ECG) changes following a 100 mile ultra-marathon and demonstrated an increase in the summated R wave in V1 and S wave in V5, J point elevation in V1, partial right bundle branch block (RBBB), T wave inversion in lead V1 and early repolarisation pre to post-race pointing to changes in the right-sided electrical conduction system. Nevertheless, the use of right-sided ECG leads, focusing on the right heart, have not been employed in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Third, several parameters measured in the present study could be significantly influenced not only by altitude, but also by the physical activity associated with trekking. However, previous studies reported that even after long‐distance running for several days, there was a decrease or no change in cardiac strain data in healthy participants (George et al., ; Lord et al., ; Nottin et al., ). Thus, exposure to high altitude seems to be the main trigger of the cardiac changes observed in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…As a consequence, repetitive bouts of myocardial damage due to exercise without a complete recovery may translate into an adverse arrhythmic remodeling, exposing the athlete to the risk of sudden cardiac death . However, the consequences of ultra‐endurance sports activity on the heart rhythm and on ECG have not been entirely understood, although an electrical instability of the ventricular myocardium and right‐sided acute changes in ECG were found in athletes after endurance races . Furthermore, few studies have collected data with 12‐lead ECG in athletes running an ultramarathon.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, the consequences of ultra-endurance sports activity on the heart rhythm and on ECG have not been entirely understood, although an electrical instability of the ventricular myocardium and right-sided acute changes in ECG were found in athletes after endurance races. [5][6][7] Furthermore, few studies have collected data with 12-lead ECG in athletes running an ultramarathon. Therefore, the aim of this study was to evaluate by 12-lead ECG the acute effects of an ultramarathon on heart rhythm and on ECG signs of right ventricular overload.…”
mentioning
confidence: 99%